Exploring the use of SIBIKU multimedia to enhance learning participation among deaf students in a special school context - Nurina Ayuningtyas; Ahmad Fajri Lutfi (Journal of Artificial Intelligence in Education & Learning Innovation, 2026)
Background: Observations at SLB C YPALB Perwari Kuningan indicate low motivation and limited participation among deaf students during learning activities. Interactive multimedia such as SIBIKU is expected to address these challenges. Objectives: This study aims to (1) examine the implementation of SIBIKU multimedia in learning, (2) analyze students’ responses, and (3) evaluate changes in students’ learning participation and vocabulary acquisition. Methods: This study employed a descriptive qualitative design with a field-based approach. Participants were selected using purposive sampling, consisting of one teacher and deaf students involved in computer learning activities. Data were collected through participatory observation, semi-structured interviews, and documentation. The main instrument was the researcher, supported by observation and interview guidelines. Data were analyzed using thematic analysis following Miles and Huberman’s model, including data reduction, data display, and conclusion drawing, with triangulation to ensure validity. Results: The findings show that SIBIKU multimedia enhances student participation, as indicated by (1) increased attention to learning media, (2) active imitation of sign language movements, (3) higher frequency of student interaction and turn-taking, and (4) greater engagement in learning tasks such as word-guessing activities. Students also demonstrated improved motivation and more independent learning behavior. Conclusions: SIBIKU multimedia provides a visually rich, interactive learning environment that effectively increases participation and engagement among deaf students, making it a promising tool for inclusive education.